2021
DOI: 10.3389/fonc.2020.579053
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Long Non-Coding RNAs as Regulators of NANOG Expression in the Development of Oral Squamous Cell Carcinoma

Abstract: NANOG is a stem cell transcription factor that is believed to play an important role in the development of oral squamous cell carcinoma (OSCC), but there is limited data regarding the role of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) in the regulation of NANOG expression. We therefore analyzed expression of NANOG, NANOG-regulating miRNAs and lncRNAs in OSCC cancerogenesis, using oral biopsy samples from 66 patients including normal mucosa, dysplasia, and OSCC. Expression analysis of NANOG, miR-34a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It was noted that expression of NANOG increased with the grade of dysplasia. The importance of NANOG was also confirmed in the study by Grubelnik et al [31], which stated that this marker can be used to differentiate dysplasia grades. NANOG protein detection has a diagnostic potential for oral high-grade dysplasia, distinguishing it from low-grade dysplasia and non-neoplastic reactive lesions.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 67%
“…It was noted that expression of NANOG increased with the grade of dysplasia. The importance of NANOG was also confirmed in the study by Grubelnik et al [31], which stated that this marker can be used to differentiate dysplasia grades. NANOG protein detection has a diagnostic potential for oral high-grade dysplasia, distinguishing it from low-grade dysplasia and non-neoplastic reactive lesions.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 67%
“…The miR-21, miR-181b, miR-345, miR-549 and miR-205, were found to be overexpressed both in progressive dysplasia and OC [292]. Another study reported up-regulation of miR-145, lncRNA RoR, and SNHG1 and downregulation of miR-34a from low-grade to high-grade dysplasia and, finally, to OC during carcinogenesis [293]. The lncRNA FGD5-AS1 inhibits NF-kB signaling, and gets downregulated in chronic periodontal samples as compared to the healthy tissues [294].…”
Section: Ncrnas In Oral Cancer Progressionmentioning
confidence: 97%